Implementasi Prinsip Syariah Dalam Operasional Bank Umum Syariah dan BPR Syariah: Suatu Studi Komparatif Hukum Perbankan - Imon, Syarah Adilla (Media Hukum Indonesia (MHI), 2025)
This research discusses in depth the application of sharia principles in the operational activities of two types of Islamic banking institutions in Indonesia, namely Islamic Commercial Banks (BUS) and Islamic Rural Banks (BPRS). The main focus of this study is to compare the extent to which the two types of banks implement sharia principles in every banking activity, including the use of types of contracts that are in accordance with Islamic sharia provisions. The basic principles of Islamic banking require that all transactions be free from elements of usury (interest), gharar (uncertainty), and maysir (speculation), and are based on legal contracts according to Islamic law such as murabahah (sale and purchase), mudharabah (profit sharing), musyarakah (partnership), ijarah (rent), and so on. BUS has a wider operational scope because it can raise funds and distribute them both on a large scale and across sectors, while BPRS is only allowed to serve micro and small businesses and is prohibited from activities such as forex and current account services. This difference has direct implications for the variety of contracts that can be used and the implementation mechanism in the field. This research is expected to provide academic and practical contributions in the development of the Islamic banking legal system in Indonesia, as well as an evaluation material for regulators in harmonising sharia operational standards in all types of Islamic banking institutions